Libras in childschool education: proposal of criteria for the elaboration of a teaching plan for Libras in regular schools - Carvalho, Andréa Guimarães; Brasil, Ynara Julia dos Santos (The ESPecialist, 2022)
This article aims to propose or suggest criteria that guide the development of a teaching plan for Libras, whether L1 or L2, which is more appropriate and meaningful for children in the school environment. The investigations, of qualitative and bibliographic character, generated reflections and perspectives that are currently presented in the literature that involves this theme in the area of ​​early childhood education. For that, the discussions were based on theorists such as Quadro e Cruz (2011), Gesser (2010), Vygotsky (1997) among others. The results showed that in the development of a teaching plan for Libras, L1 or L2 for children, the following criteria are suggested: consider the processes of language acquisition and language development; what stage of development and cognition the children are in, to identify what is appropriate and what needs to be acquired and also the number of hearing and deaf children in the school context, noting whether more methodological teaching approaches such as L1 or like L2. In addition, it was found that in academic production in the area of ​​Libras, very few works were found that guide the practice of teaching Libras for early childhood education. Keywords: Libras in early childhood educativo, Planning in the teaching of Libras, Education and language development.